2018
DOI: 10.1177/1098612x18805879
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of furosemide after intravenous, oral and transdermal administration to cats

Abstract: Objectives The aim of this study was to determine the pharmacokinetics of furosemide in cats following intravenous (IV), oral and transdermal administration. Methods This study used six healthy adult cats in a three-phase design to compare plasma furosemide concentrations in cats that received one IV 2 mg/kg dose of furosemide, one oral 2 mg/kg dose of furosemide and 3 days of q12h dosing with 2 mg/kg furosemide transdermally applied to the ear pinna. Results After IV administration the elimination half-life w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…In addition, furosemide has been reported to treat edema in heartwater (cowdriosis) (Shakespeare et al., 1998) and to reverse tissue hypoxia in septic acute kidney injury (Iguchi et al., 2019) and to prevent postoperative pulmonary edema in cardiovascular surgeries in sheep (DiVincenti et al., 2014). The pharmacokinetics of furosemide was determined in horses (Dyke et al., 1996; Johansson et al., 2004), dog (Hirai et al., 1992), camel (Ali et al., 1998), piglets (Miceli et al., 1990), and cats (Sleeper et al., 2019). The studies have shown apparent differences in the effects and pharmacokinetics of furosemide for different routes of the administration among species (Ali et al., 1998; Johansson et al., 2004; Sleeper et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, furosemide has been reported to treat edema in heartwater (cowdriosis) (Shakespeare et al., 1998) and to reverse tissue hypoxia in septic acute kidney injury (Iguchi et al., 2019) and to prevent postoperative pulmonary edema in cardiovascular surgeries in sheep (DiVincenti et al., 2014). The pharmacokinetics of furosemide was determined in horses (Dyke et al., 1996; Johansson et al., 2004), dog (Hirai et al., 1992), camel (Ali et al., 1998), piglets (Miceli et al., 1990), and cats (Sleeper et al., 2019). The studies have shown apparent differences in the effects and pharmacokinetics of furosemide for different routes of the administration among species (Ali et al., 1998; Johansson et al., 2004; Sleeper et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacokinetics of furosemide was determined in horses (Dyke et al., 1996; Johansson et al., 2004), dog (Hirai et al., 1992), camel (Ali et al., 1998), piglets (Miceli et al., 1990), and cats (Sleeper et al., 2019). The studies have shown apparent differences in the effects and pharmacokinetics of furosemide for different routes of the administration among species (Ali et al., 1998; Johansson et al., 2004; Sleeper et al., 2019). We hypothesized that intramuscular (IM) and subcutaneous (SC) injections of furosemide would be used as an alternative route in sheep by the reach to similar total exposure (area under the curve) comparable to those achieved by intravenous (IV) administration.…”
Section: Introductionmentioning
confidence: 99%
“…In the body, furosemide moves across the renal tubule from the plasma to the lumen of the nephron; thus, furosemide acting on henle's loop of renal tubule should have a short duration of effects if its half-life is short (7). After IV administration, the C max was slightly higher than that after OUT or FS-ODF administration, whereas the T 1/2 and T max were slightly lower.…”
Section: Discussionmentioning
confidence: 95%
“…It is used in animals for the treatment of pulmonary edema, udder edema, hypercalciuric nephropathy, uremia, and hypertension. Additionally, it reduces the incidence of sterile hemorrhagic cystitis associated with cyclophosphamide administration in dogs and is used as adjunctive therapy in hyperkalemia (2)(3)(4)(5)(6)(7)(8)(9)(10). The PK/PD properties of loop diuretics, including furosemide after IV and PO administration, have been well investigated in both human and veterinary medicine (5,8,(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation